“Tiempo imprevisto” - Diaz Suarez, Fiorella Marysol (2020)
"Tiempo Imprevisto" is an autobiographical documentary whose main objective is to show the changes that the main character went through due to the obligatory social isolation; presenting their emotions, thoughts, desires, routines, doubts and uncertainty, and how their relationships with family, physical contact, space, amongst others, have had to adapt to cope with the situation. This documentary is divided into 4 important points that support the work: i) Background of the work, where the situation is contextualized and the basic concepts that are developed throughout the documentary are presented. ii) The Communication Proposal that shows the casting proposal, spaces, visual, sound, editing, among others. iii)Support through texts, references and data is the basis for each decision made for therealization of "Tiempo Imprevisto". iv) the Recommendations explain the positive factors that contributed to the making of the film as well as future suggestions.